1967
DOI: 10.1177/004051756703700406
|View full text |Cite
|
Sign up to set email alerts
|

Wet-Fixation Durable-Press Process—Reactions with Cellulose

Abstract: The nature and extent of the reactions involved in the two-step, wet-fixation durablepress process of Getchell and other processes have been determined by means of a periodate oxidation method. The wet-fixation, durable-press process is shown to differ from the acid colloid process and other wet-fixation procedures. The variations show up in terms of the concentration of the methoxymethylol compound and reactant fixed on the fiber and the extent to which covalent crosslinking of cellulose occurs.The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…structure (noncollapsed) in the fiber (by comparison to that cross-linked by the pad-dry-cure process). This is shown by the higher moisture regain reported by Hollies [ 10 ] and Honold [12], by the higher accessibility of periodate reported by O'Brien et al [ 14 ) , and by the rather complete expansion of thin cross sections of wet-fix cotton (either fixed-only or fixed and cured) when subjected to the methacrylate expansion technique (pad-dry-cure compositions did not expand). These expansion patterns reported by Rollins [ 18] for wet-fix cottons characterized by 4-6% add-ons are in contrast to earlier results reported by Hollies [10] for samples with substantially higher add-ons.…”
Section: Discussionmentioning
confidence: 93%
“…structure (noncollapsed) in the fiber (by comparison to that cross-linked by the pad-dry-cure process). This is shown by the higher moisture regain reported by Hollies [ 10 ] and Honold [12], by the higher accessibility of periodate reported by O'Brien et al [ 14 ) , and by the rather complete expansion of thin cross sections of wet-fix cotton (either fixed-only or fixed and cured) when subjected to the methacrylate expansion technique (pad-dry-cure compositions did not expand). These expansion patterns reported by Rollins [ 18] for wet-fix cottons characterized by 4-6% add-ons are in contrast to earlier results reported by Hollies [10] for samples with substantially higher add-ons.…”
Section: Discussionmentioning
confidence: 93%
“…Some previous studies [1][2][3] have shown that the finishing process, the swelling state of the crosslinked fibers, and the crosslinking agents can affect the crease recovery properties of crosslinked fabrics. Our previous report 4 showed that some physical properties were improved by the polymerization of crosslinking agents in the treated fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Direct Red 81 with a molecular weight of 676 g/mol was used to study the pore structures of the steeped-procedure-treated fabrics. We studied the pore structure by using the following diffusion equation: 6,7 a ϭ a e ͓1 Ϫ exp͑ Ϫ kC 0 t͔͒ n ϭ a e ͓1 Ϫ exp͑ Ϫ kЈt͔͒ n (1) where a is the absorption of the dye on cotton in time t, a e is the equilibrium absorption at t 3 ϱ, k is the specific rate constant, kЈ is the rate constant, C 0 is the concentration of cotton in a finite bath, and n is the structural diffusion resistance constant. The higher n is, the larger the pore size is of the treated fabric.…”
Section: Introductionmentioning
confidence: 99%
“…Prahl [6] showed correlations between physical parameters of the polymer deposit and final fabri,c characteristics. In wet polymer-deposition studies [3,4,5] (so-called wet fixation processes), the swelling of the fiber and thereby, its penetration by the monomer and the final polymer distribution are emphasized. In still another direction, the latent reactivity of the deposited polymer with the cross-linking agent is being in-, vestigated [9,10] .…”
Section: Introductionmentioning
confidence: 99%